Analisis Arsitektur Jaringan Pada Topologi Bus - Diyas Bellia Putri; M. Nabil Makarim; Gunawan Gunawan; M. Rosyid Ridho; Didik Aribowo (Router : Jurnal Teknik Informatika dan Terapan, 2024)
Computer networks are an important part of modern life, enabling the efficient exchange of information and resources between devices. One type of network topology that is commonly used is a bus topology. The bus topology has a simple structure and is easy to implement, making it an attractive choice for a variety of applications. The main finding of this research is that the bus topology has several advantages and disadvantages. The advantages of bus topology include low cost, ease of installation, and scalability. Disadvantages of bus topology include limited performance, low reliability, and the potential for data collisions.